Experimental investigation of a spark ignition engine using blends of biogas. Issue 4 (20th March 2020) - Arul Peter, A.; Chandrasekaran, M.; Prakash, P.; Kumar, T. Vinod; Vivek, P.
ABSTRACT: Biogas from cow dung is one of the best fuels that readily mixes with gasoline and yields less emission and better performance on gasoline engines. In this study, an attempt has been made experimentally on a gasoline engine operating with enriched and compressed biogas blends B10, B20 and gasoline. A significant increase in specific consumption and reduction in brake thermal efficiency of the engine was observed. Exhaust gas emissions were measured and analysed for hydrocarbons (HC), carbon dioxide (CO2 ), carbon monoxide (CO) and oxides of nitrogen (NOX ) at an engine speed of 2000rpm. The concentrations of CO, CO2 and HC emission were found to be decreased and increased trend in NOx for biogas blends.